The Risks and Opportunities from Globalisation - Wayne Stevens (New Zealand Government, The Treasury, 2007)
Globalisation, being the trend towards increasing global economic integration, is one of the largest forces, if not the largest force, affecting world economies at present. The current period of global economic integration is unprecedented and the pace and extent of globalisation will continue to have major ramifications for the world, regional and New Zealand economy. It is highly unlikely that the process of increasing global economic integration will reverse. Globalisation offers both risks and opportunities. New Zealand can achieve significant benefits from future globalisation. The challenge will be to ensure that we are one of the adaptive economies that can successfully adopt policies that maximise the benefits and minimise the risks. In responding to globalisation it is necessary to consider policies that promote a globally competitive environment for New Zealand businesses. Further consideration of how domestic policy settings look when viewed through an international competitiveness lens is imperative. This report offers preliminary views on what some of these policies should be. It does not answer fully the question of how New Zealand should respond to the challenges and opportunities of globalisation but it outlines initial views in order to stimulate debate on this topic.
Keywords: 330; Globalisierung; Wirtschaftswachstum; Internationale Wirtschaft; Wirkungsanalyse; Neuseeland